Induction of immunogenicity by live attenuated Leishmania donovani centrin deleted parasites in dogs. - Fiuza, Jacqueline Araújo (2013)
Fundação Oswaldo Cruz. Centro de Pesquisas René Rachou. Laboratório de Imunologia Celular e Molecular. Belo Horizonte, MG, Brazil/Universidade Federal de Minas Gerais. Departamento de Parasitologia. Belo Horizonte, MG, Brazil/Division of Emerging and Transfusion Transmitted Diseases. Office of Blood Research and Review. Center for Biologics Evaluation and Research. Food and Drug Administration. Bethesda, MD, USA